Effect of Titanate Coupling Agent on Mechanical Properties of Rice Husk Polypropylene Composites - Kumar, Vinay; Sinha, Shishir; Singh Saini, Manohar; Kanungo, B.K. (Asian Journal of Chemistry, 2010)
Easy availability, low cost and biodegradable nature of lignocellulosic materials necessitated the development of thermoplastic composites, based on commodity plastic such as poly propylene (PP). It can be reinforced with rice husk, a type of lignocellulosic material abundantly available in nature. Preheating of rice husk and its proper size is beneficial for achieving good mechanical strength. Titanate coupling agent is very useful for enhancement in mechanical properties of rice husk polypropylene composites. These composite have potential as good building material.